2019
DOI: 10.1292/jvms.19-0305
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of antibiotic resistance in <i>Escherichia coli</i> isolated from wild cranes on the Izumi plain in Kagoshima prefecture, Japan

Abstract: The prevalence of antibiotic resistance in 376 Escherichia coli (E. coli) isolates from fecal samples of Hooded and White-naped cranes was investigated on the Izumi plain in Kagoshima prefecture, Japan, during winter 2016 and 2017. Resistance to oxytetracycline, ampicillin, and nalidixic acid were observed in 10.9%, 3.1–4.4%, and 2.1–7.7% of isolates, respectively. Since the previous surveillance in 2007, isolation rates of antibiotic-resistant E. coli recovered from wild cranes have remained at significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The E. coli isolated from wild and domestic animals in the area around the Salakphra Wildlife Sanctuary were resistant to ten antibiotics. Antibiotic resistance in commensal E. coli has been reported in various wild mammals worldwide, including birds [40][41][42][43], rodents [41], ungulates [44], primates [45,46], boars [47], foxes [48], rabbits [48,49], and deer [48,50]. We found that E. coli isolates from deer were resistant to AMP.…”
Section: Discussionmentioning
confidence: 72%
“…The E. coli isolated from wild and domestic animals in the area around the Salakphra Wildlife Sanctuary were resistant to ten antibiotics. Antibiotic resistance in commensal E. coli has been reported in various wild mammals worldwide, including birds [40][41][42][43], rodents [41], ungulates [44], primates [45,46], boars [47], foxes [48], rabbits [48,49], and deer [48,50]. We found that E. coli isolates from deer were resistant to AMP.…”
Section: Discussionmentioning
confidence: 72%
“…Also, 376 recovered E. coli isolates from Hooded and White-naped cranes in Japan were found resistant to oxytetracycline, ampicillin and nalidixic acid antibiotics. A high resistance level was also recorded against tetracycline followed by sulfamethoxazole, ampicillin, trimethoprim and ciprofloxacin in most E. coli isolates (Suenaga et al 2019 ). Furthermore, 87 of 88 egret’s and 53 of 55 cattle E. coli isolates were found to have MDR against more than one antimicrobial.…”
Section: Discussionmentioning
confidence: 99%
“…Among these crane species, both hooded cranes and white-naped cranes are classified as vulnerable species on the International Union for Conservation of Nature (IUCN) Red List (BirdLife International., 2016. The Izumi plain has thus been targeted as an ideal location to perform a range of crane conservation activities, including infectious disease surveillance (Khalil et al, , 2021Kitadai et al, 2010Kitadai et al, , 2012Maeda et al, 2001;Nakagawa et al, 2018;Okuya et al, 2015Okuya et al, , 2017Ozawa et al, 2015Ozawa et al, , 2019Suenaga et al, 2019;Takase et al, 2020). The newly discovered CrAdV-1 is a cause of concern as a potential pathogen for which only very limited information has been established.…”
Section: E2801mentioning
confidence: 99%